The Role of Lectin Receptors and Their Ligands in Controlling Allergic Inflammation - Peters, Karin; Peters, Marcus (Frontiers in Immunology, 2021)
So far more than fifty c-type lectin receptors (CLR) are known and identified. Moreover, we know the group of galectins and Sialic acid-binding immunoglobulin-type lectins that also belong to the carbohydrate binding receptors of the immune system. Thus the lectin receptors form the largest receptor family among the pathogen recognition receptors. Just like the toll-like receptors (TLRs) the CLR do not only recognize foreign but also endogenous molecules. In contrast to TLRs, which have a predominantly activating effect on the immune system, lectin receptors also mediate inhibitory signals. They play an important role in innate and adaptive immunity for the induction, regulation and shaping of the immune response. The hygiene hypothesis links enhanced infection to protection from allergic disease. Yet the microbial substances that are responsible for mediating this allergy-protective activity still have to be identified. Microbes contain both ligands binding to TLRs but also carbohydrates that recognized by CLR and other lectin receptors. In the current literature the CLR are often recognized as bad guys in allergic inflammation, because some glycoepitopes of allergens were shown to bind to CLR facilitating their uptake and presentation. On the other hand, there are many reports revealing sugar moieties to be involved in immune regulation. In this review we will summarize what is known about the role of carbohydrates interaction with c-type lectins and other sugar recognizing receptors in anti-inflammation with a special focus on the regulation of the allergic immune response.